Pulse Clean and Regeneration Control Device in Ceramic Filter - Xilian DIAO; Haiming LIU; Yang LIU (Institute of Advanced Engineering and Science, 2013)
This article developed a 6120-type diesel particulate filter pulse clean and regeneration control system with a high efficiency, simple reliable use. And it has determined the spray nozzle diameter, the injection distance, the injection pressure, the pulse width, the injection time of five factor optimal fit experiment parameter. This control system can flow the type honeycomb ceramics filter to the wall to carry on the test and the research of the filtration and the regeneration; It can realize the filter filtration and the regeneration change work. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3232